PEMANFAATAN SEARCH ENGINE GOOGLE DALAM PEMENUHAN KEBUTUHAN INFORMASI MAHASISWA PRODI PERPUSTAKAAN DAN ILMU INFORMASI UNIVERSITAS NEGERI PADANG - M. Aries Fiqri; Marlini Marlini (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study aims to describe how the use of the Google search engine in fulfilling information needs by students of the Library and Information Science Study Program, Padang State University. This type of research is quantitative research with descriptive methods. The population in this study were 288 Library and Information Science students, and a sample of 75 people. Sampling was determined based on purposive sampling technique which is a sampling technique with certain considerations. The research data was obtained by distributing questionnaires through the Google Form application by distributing the questionnaire links to respondents. Data analysis was carried out descriptively by calculating relative frequency and proportion formulas. The score results obtained in the use of the Google search engine in fulfilling the information needs of students of Library and Information Science Study Program, Padang State University is 2.90 which is on an interval scale of 2.50 – 3.24, so it can be seen that the use of the Google search engine in fulfilling needs Information on students of the Library and Information Science Study Program, Padang State University, is in the good category.